2012
DOI: 10.1039/c2dt31475d
|View full text |Cite
|
Sign up to set email alerts
|

Variable coordination of a chiral diphosphine containing an amidinium/NHC group within its backbone: μ-P,P′, κ2-P,P′ and κ3-P,C,P′ coordination modes

Abstract: A diphosphine ligand (1·HPF(6)), which is a potential precursor to a PC(NHC)P pincer, with a backbone containing two phenylene groups and a central bicyclic 4-aza-2-azoniabicyclo[3.2.1]oct-2-ene unit has been synthesised and coordinated to Pd(II) and Pt(II) to give trans-[M(κ(2)-P,P'-)Cl(2)]PF(6) where M = Pd (2) or Pt (3a). Single-crystal structure determinations of 2 and 3a show the complexes to be isostructural with the diphosphine coordinated in a trans-spanning fashion and the amidinium unit being protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 122 publications
0
18
0
Order By: Relevance
“…Tridentate triamine ligands have advantages, including ready availability, relatively low cost, and low toxicity . Various metal complexes with camphor-based pyridine ligands have also been used for asymmetric catalytsis and tested for biomolecular interactions or antitumor activity. …”
Section: Introductionmentioning
confidence: 99%
“…Tridentate triamine ligands have advantages, including ready availability, relatively low cost, and low toxicity . Various metal complexes with camphor-based pyridine ligands have also been used for asymmetric catalytsis and tested for biomolecular interactions or antitumor activity. …”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] A solution to this problem was found through the use of bulky trialkylphosphine ligands [44][45][46][47] and more recently the use of platinum N-heterocyclic carbene complexes. [48][49][50][51][52] These sterically encumbered catalysts can impart high levels of selectivity on the reactions. Of note was the development of the (dvs)Pt-Pt-Bu 3 catalyst which exhibits excellent catalytic activity and a high level of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Employing a similar methodology, Newman et al have synthetized salts containing aryl groups bearing electron donor groups as precursors of tridentate ligands. 98,99 In 2005, a method was patented in which orthoesters were used as precursors to prepare cationic polymers bearing cyclic non-aromatic units containing an amidinium group, such as tetrahydrodiazepinium salts, among others. 100 One strategy to introduce a cyclic amidinium group into a side chain of the polymer is either to start out from a polymer which bears an orthoester group 29, preferably an ethyl orthoester, in the side chain and allow it to react with an N,N'-dialkyl-α,ω-alkanediamine, or to start out from a polymer which bears the diamine function 30 in the side chain and allow it to react with an orthoester, preferably an ethyl orthoester (Scheme 31).…”
Section: Scheme 30mentioning
confidence: 99%
“…The first example has been reported by Cetinkaya et al, who demonstrated that in situ generated 1,3dibenzyltetrahydrodiazepin-2-ylidene palladium complexes are very effective in Suzuki-Miyaura coupling reactions of deactivated aryl chlorides. 95 Since then, seven-membered NHC complexes have been tested for catalytic transformations such as the Heck type cross-coupling, 96,105,122 Suzuki type reactions, 10,99 hydration of internal alkynes, 123 hydrosilylation, 99,104 catalytic hydrogenation 106 and transfer hydrogenation. 124,125 The important results achieved with complexes bearing expanded ring NHC ancillary ligands in catalytic transformations have been attributed to the strong binding of the electron-rich carbene to the metal center that helps the metal retain its ligand, which provides the compound a longer catalyst life time, thus affording enhanced activity 106,126 Cavell et al have reported the synthesis of the first eight-membered ring (diazocanylidene) NHCs 43 through the reaction of the corresponding cyclic amidinium salt 44 with KHMDS.…”
Section: Scheme 41mentioning
confidence: 99%